Catch me while you scan: Primary ovarian pregnancy - Sweta Singh; Prashanta Kumar Rout; Pavithra Ayyanar (Wolters Kluwer Medknow Publications, 2021)
Primary ovarian pregnancy is rare, accounting for 0.5%-3.0% of all ectopic gestations. It was earlier diagnosed by the classical Spiegelberg's criteria. Ultrasonographic diagnostic criteria have now been described for preoperative diagnosis. We report a case of primary ovarian pregnancy in a 30-year-old woman, where the diagnosis was made preoperatively, and discuss the challenges in diagnosis and management for optimal patient outcomes.